2007
DOI: 10.4315/0362-028x-70.11.2541
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antibiogram, Staphylococcal Enterotoxin Productivity, and Coagulase Genotypes among Staphylococcus aureus Isolated from Animal and Vegetable Sources in Korea

Abstract: Staphylococcal food poisoning is caused by enterotoxin-producing Staphylococcus aureus. We investigated the prevalence of such organisms in samples of bovine mastitic milk (n = 714), raw meat (n = 139), and vegetables (n = 616). We determined the degrees of relatedness of isolates as indicated by antibiogram, staphylococcal enterotoxin (SE) productivity, and coagulase gene restriction fragment length polymorphism analysis. We examined 297 S. aureus isolates and found SE production in 57 (31.8%), 4 (7.8%), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 31 publications
3
12
1
Order By: Relevance
“…The results of two studies also showed that the prevalence of SEA encoding gene in isolated strains were 15.4% and 18.8% (27). A study by Moon et al on three groups of food revealed that the contamination of meat products with S. aureus was the highest 36% (28). The above results are almost similar to those of the current study.…”
Section: Discussionsupporting
confidence: 90%
“…The results of two studies also showed that the prevalence of SEA encoding gene in isolated strains were 15.4% and 18.8% (27). A study by Moon et al on three groups of food revealed that the contamination of meat products with S. aureus was the highest 36% (28). The above results are almost similar to those of the current study.…”
Section: Discussionsupporting
confidence: 90%
“…The likelihood of microbial disease emergence and spread is becoming higher with the enhancement of world globalization interconnectedness; the spread of antibiotic resistant bacteria with food products is a major concern. Many S. aureus population have developed resistance to commonly used antibiotics, e.g., penicillin, ampicillin due to the wide use of the ß-lactams, particularly for treatment of bovine mastitis (Moon et al, 2007;Peles et al, 2007). It is apparent from the present study that in Vietnam appropriate public health and food hygiene practices during production, transportation, storage and retailing should be implemented to reduce the risk of S. aureus related food poisoning.…”
Section: Resultsmentioning
confidence: 91%
“…Thus, our limited number of sample analysis indicates a high prevalence of enterotoxin producing S. aureus strains in the ready-to-eat foods in Vietnam. Moon et al (2007) reported that mastitic milk and raw meat samples in Korea contained 31.8% and 7.8% SE positive S. aureus, respectively. A higher abundance (47%) of SE positive strains among total S. aureus isolates has also been reported in a recent survey from ready-toeat foods in Korea (Oh et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Swabs were transferred to the TSB containing 7% NaCl. The isolates were subcultured on MSA and incubated at 37°C for 24 hrs [22].…”
Section: Nasal Swabsmentioning
confidence: 99%